Functional assessment of movements of men in the first period of adulthood who are engaged in health fitness - Grygus, Igor; Dolishnyi, Mykhailo (Journal of Education, Health and Sport, 2022)
Actuality. Over the past decades, a body of scientific knowledge has been accumulated on the problem of studying the state of human motorics in mature age during the process of physical exercises. Data from numerous studies indicate that impaired posture of people in mature age, a decrease in the level of physical fitness is a relevant today problem. Research objective is to determine the motor preparedness of men aged 26–31 years old who are engaged in health fitness using the Functional Movement Screen test system. Research results. At the stage of the ascertaining experiment, it was planned to conduct a functional assessment of physical fitness and movements of men aged 26–28 years old (n=16) and 29–31 years old (n=17) involved in the experiment. It was found that in test 1 (“Deep Squat”), where a deep squat was performed, most men (87.87%) received high scores (2 or 3 points), which is a good result. When stepping over the barrier (“Hurdle Step” – test 2), a significant part (69.7%) experienced problems with balance and coordination and received only 1 point. None received 3 points, which indicates the need to improve these skills. When performing a lunge in test 3 (“In-Line Lung”), more than half (57.58%) of the participants received scores of 2 or 3 points, which indicates a satisfactory ability to perform such an exercise. Test 4 (“Shoulder Mobility”) on the mobility of the shoulder girdle was performed by half of the participants (45.45%) with 1 point, that is, they had problems with the mobility of the shoulder girdle. Almost half (45.45%) of the subjects performed the raising of straight leg (“Active Straight Leg Raise” – Test 5) with limited flexibility, but there was also a significant number (45.45%) who scored 2 points. When performing Test 6 (“Trunk Stability Push Up”), the majority of participants (81.82%) showed a high level of body strength and stability, receiving 2 or 3 points. Also, more than 80% of the participants demonstrated satisfactory or high rotational stability, receiving 2 or 3 points for Test 7 (“Rotary Stability”). Conclusions. It was found that men aged 26-28 had better overall functional fitness compared to men aged 29-31. This is confirmed by higher average values of the overall functional assessment compared to men aged 29-31, as evidenced by a difference of 2.16 points (p<0.01).